Time to metastasis as a prognostic factor in metastatic urothelial carcinoma: results from the ARON-2 study - Renate Pichler; Gerald Klinglmair; Kirstin Binz; Enrique Grande; Alina Pirshtuk; Hideki Takeshita; Yüksel Ürün; Javier Molina-Cerrillo; Zin W. Myint; Alfonso Gómez de Liaño; Augusto Mota; Alessia Salfi; et al. (Clinical & Experimental Metastasis, 2025)

The transcriptional mechanism behind Mimosa pudica leaf folding in response to mechanical disturbance - Matteo Buti; Alice Checcucci; Chiara Vergata; Luciana Renna; Susanna Pollastri; Francesco Loreto; Stefano Mancuso; Federico Martinelli (Planta, 2025)
Main conclusions Repeated stress in Mimosa pudica reduces photosystem efficiency, alters gene expression, shifting from flavonoid biosynthesis to stress resistance pathways, offering insights for sustainable plant stress defense strategies. Abstract Mimosa pudica is a plant known for its ability to fold leaves in response to mechanical disturbances, which serves as a visible phenotypic stress marker. Leaf folding response occurs with a timing and an intensity that vary depending on the stimulus. This adaptive behavior may function as a defense mechanism, helping plant resist herbivores and environmental stressors. In this study, we investigated the gene regulatory networks underlying M. pudica leaf closure following single and multiple mechanical disturbances (whole pot drops). Chlorophyll fluorescence was measured as fast phenotypic indicator of transient or permanent photochemical damage, and transcriptional responses were measured to identify the key genes regulating phenotypic changes after single or multiple drops. A progressive reduction of the quantum yield of PSII revealed a lower electron transport rate in leaves subjected to one or more drops, which may indicate the onset of energy shortage, potentially caused by limited ATP availability that constrains both leaf movement and photosynthesis. The transcriptomic profiles revealed larger differences when plants were subjected to multiple drops than to a single drop, with respect to unstressed controls. Interestingly, following a single drop, the majority of up-regulated genes were associated with the flavonoid biosynthetic pathway. After multiple drops, however, genes associated with biotic and abiotic stress resistance pathways were predominantly up-regulated. These findings provide new insights into the gene regulatory networks driving stress-induced movements in M. pudica leaves and lay the groundwork for developing sustainable strategies for plant stress defense.

Prognostic immunotherapy score (PIS) in patients with advanced urothelial carcinoma treated with pembrolizumab: real-world data and validation from ARON-2 dataset - Alessandro Rizzo; Anas Zayed; Elsa Vitale; Sebastiano Buti; Hideki Takeshita; Simon Crabb; Giandomenico Roviello; Emmanuel Seront; Jose Carlos Tapia; Sarah Scagliarini; Lazar Popovic; Ray Manneh Kopp; et al. (Clinical & Experimental Metastasis, 2025)

Concomitant medications in patients with metastatic urothelial carcinoma receiving enfortumab vedotin: real-world data from the ARON-2EV study - Ondřej Fiala; Sebastiano Buti; Kazutoshi Fujita; Alfonso Gómez de Liaño; Wataru Fukuokaya; Takahiro Kimura; Takafumi Yanagisawa; Patrizia Giannatempo; Martin Angel; Alessia Mennitto; Javier Molina-Cerrillo; Maria T. Bourlon; et al. (Clinical & Experimental Metastasis, 2025)
Patients with metastatic urothelial carcinoma (mUC) are typically elderly and often have other comorbidities that require the use of concomitant medications. In our study we evaluated the association of concomitant use of antibiotics (ATBs), proton pump inhibitors (PPIs), corticosteroids, statins, metformin and insulin with patient outcomes and we validated the prognostic role of a concomitant drug score in mUC patients treated with enfortumab vedotin (EV) monotherapy. Data from 436 patients enrolled in the ARON-2 EV retrospective study were analyzed according to the concomitant medications used at baseline. Finally, the patients were stratified into three risk groups according to the concomitant drug score based on ATBs, corticosteroids and PPIs. Statistical analysis involved Fisher exact test, Kaplan–Meier method, log-rank test, and univariate/multivariate Cox proportional hazard regression models. Inferior survival outcomes were observed in ATB users compared to non-users (OS: 7.3 months, 95%CI 5.0 − 12.3 vs 13.7 months, 95%CI 12.2 − 47.3, p = 0.001; PFS: 5.1 months 95%CI 3.3 − 17.7 vs 8.3 months, 95%CI 7.1 − 47.3, p = 0.001) and also in corticosteroid users compared to non-users (OS: 8.4 months, 95%CI 6.6 − 10.0 vs 14.2 months, 95%CI 12.7 − 47.3, p < 0.001; PFS: 6.0 months 95%CI 4.6 − 7.9 vs 8.9 months, 95%CI 7.2 − 47.3, p = 0.004). In the Cox multivariate analysis, the concomitant drug score was a significant factor predicting both OS (HR = 1.32 [95% CI 1.03 − 1.68], p = 0.026) and PFS (HR = 1.23 [95% CI 1.01 − 1.51], p = 0.044). Our findings suggest detrimental impact of concomitant use of ATBs and corticosteroids on survival outcomes and the prognostic utility of the concomitant drug score in previously treated mUC patients receiving EV.

Pembrolizumab in patients with advanced upper tract urothelial carcinoma: a real-world study from ARON-2 project - Alessandro Rizzo; Sebastiano Buti; Patrizia Giannatempo; Samer Salah; Javier Molina-Cerrillo; Francesco Massari; Ray Manneh Kopp; Ondřej Fiala; Luca Galli; Zin W. Myint; Deniz Tural; Andrey Soares; et al. (Clinical & Experimental Metastasis, 2024)

Transcriptomic and volatilomic profiles reveal Neofabraea vagabunda infection-induced changes in susceptible and resistant apples during storage - Paolo Baldi; Matteo Buti; Valeria Gualandri; Iuliia Khomenko; Brian Farneti; Franco Biasioli; Donatella Paffetti; Mickael Malnoy (Postharvest Biology and Technology, 2024)

External validation of a red cell-based blood prognostic score in patients with metastatic renal cell carcinoma treated with first-line immunotherapy combinations - Michele Maffezzoli; Matteo Santoni; Giulia Mazzaschi; Sara Rodella; Eleonora Lai; Marco Maruzzo; Umberto Basso; Davide Bimbatti; Roberto Iacovelli; Annunziato Anghelone; Ondřej Fiala; Sara Elena Rebuzzi; et al. (Clinical & Experimental Metastasis, 2024)
Immunotherapy combinations with tyrosine-kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) had significantly improved outcomes of patients with mRCC. Predictive and prognostic factors are crucial to improve patients’ counseling and management. The present study aimed to externally validate the prognostic value of a previously developed red cell-based score , including hemoglobin (Hb), mean corpuscular volume (MCV) and red cell distribution width (RDW), in patients with mRCC treated with first-line immunotherapy combinations (TKI plus ICI or ICI plus ICI). We performed a sub-analysis of a multicentre retrospective observational study (ARON-1 project) involving patients with mRCC treated with first-line immunotherapy combinations. Uni- and multivariable Cox regression models were used to assess the correlation between the red cell-based score and progression-free survival (PFS), and overall survival (OS). Logistic regression were used to estimate the correlation between the score and the objective response rate (ORR). The prognostic impact of the red cell-based score on PFS and OS was confirmed in the whole population regardless of the immunotherapy combination used [median PFS (mPFS): 17.4 vs 8.2 months, HR 0.66, 95% CI 0.47–0.94; median OS (mOS): 42.0 vs 17.3 months, HR 0.60, 95% CI 0.39–0.92; p < 0.001 for both]. We validated the prognostic significance of the red cell-based score in patients with mRCC treated with first-line immunotherapy combinations. The score is easy to use in daily clinical practice and it might improve patient counselling.

Transgenerational effects of chromium stress at the phenotypic and molecular level in Arabidopsis thaliana - Ilaria Colzi; Cristina Gonnelli; Chiara Vergata; Gabriele Golia; Andrea Coppi; Maria Beatrice Castellani; Antonio Giovino; Matteo Buti; Tommaso Sabato; Maurizio Capuana; Alessio Aprile; Luigi De Bellis; et al. (Journal of Hazardous Materials, 2023)

Transcriptomic analysis of pollen-pistil interactions in almond (Prunus dulcis) identifies candidate genes for components of gametophytic self-incompatibility - Eva M. Gómez; Matteo Buti; Daniel J. Sargent; Federico Dicenta; Encarnación Ortega (Tree Genetics & Genomes, 2019)

Transcriptome profiling of short-term response to chilling stress in tolerant and sensitive Oryza sativa ssp. Japonica seedlings - Matteo Buti; Marianna Pasquariello; Domenico Ronga; Justyna Anna Milc; Nicola Pecchioni; Viet The Ho; Chiara Pucciariello; Pierdomenico Perata; Enrico Francia (Functional & Integrative Genomics, 2018)

A computational study of the dynamics of LTR retrotransposons in the Populus trichocarpa genome - Rosa Maria Cossu; Matteo Buti; Tommaso Giordani; Lucia Natali; Andrea Cavallini (Tree Genetics & Genomes, 2012)